Порівняння різних методів вимірювання магнітних полів у сонячних спалахах - Лозицький, Всеволод Григорович; Яковкін, І.; Кравченко, Є.; Таращук, В. (Київський національний університет імені Тараса Шевченка, 2021)
Наведено порівняння можливостей трьох методів вимірювання магнітних полів по ефекту Зеємана, які найчастіше використовуються для вивчення сонячних спалахів, а саме, методу "центрів ваги", розщеплення піків параметра Стокса V й аналізу бісекторів профілів I ± V. Коротко представлено нові дані про магнітні поля у лімбовому сонячному спалаху 14 липня 2005 р. За даними в лінії Н, усереднене магнітне поле Вeff на момент 12:02 UT досягало 850 ± 100 Гс на висоті 16 Мм. Для кількох місць спалаху знайдено слабку поляризацію різних знаків на віддалях 1,8–2,2 Å від центра лінії, яка може вказувати на надсильні локальні магнітні поля в діапазоні приблизно 85–100 кГс.

We present a comparison of possibilities of three methods of magnetic field measurements using the Zeeman effect, namely, method of "center of gravity", splitting of Stokes V peaks and analysis of bisectors of I ± V profiles. We note that first method gives very averaged data in form of effective magnetic field Beff which presents the lower limit of local magnetic field in spatially unresolved structures. Splitting of Stokes V peaks V can present local magnetic field B, but only in a case when this splitting exceeds considerably the splitting of peaks of the Stokes I gradient dI/d. Analysis of bisectors of I ± V profiles presents simple method for rapid diagnostics of magnetic field inhomogeneity. In particular, in case of really weak and homogeneous magnetic field, bisectors of I + V and I – V profiles should be parallel to each other. If these bisectors are non-parallel having some extrema, this could be an evidence of hidden presence of strong spatially unresolved magnetic field. Last method is very subtle but needs careful accounting of instrumental effects in line profiles. In this paper, we present also new data related to magnetic fields in limb solar flare of 14 July 2005. Spectral observations of this flare were carried out with the Echelle spectrograph of the Horizontal Solar Telescope of the Astronomical Observatory of Taras Shevchenko National University of Kyiv. In order to measure the magnetic fields in this flare, I ± V profiles of Н line were studied. It was found that effective magnetic field Вeff in the flare reached 850 ± 100 G on height 16 Mm. However, the spectral evidences to yet stronger local fields of 104 - 105 G range were found. In particular, for several places of the flare, a weak circular polarization of opposite signs was found in line wings on distances of 1.8-2.2 Å from line center. If this polarization to interpret as manifestations of the Zeeman effect, the corresponding magnetic field is  85–100 kG.
Comparison of different methods for magnetic field measurements in solar flares
Keywords: Сонце; сонячна активність; сонячні спалахи; ефект Зеємана; методи вимірювань; сильні і надсильні магнітні поля; Sun; solar activity; solar flares; Zeeman effect; methods of measurements; strong and superstrong magnetic fields